2014
DOI: 10.1179/1743132813y.0000000308
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnostic value of a TCD-based non-invasive ICP measurement method compared with the sonographic ONSD method for detecting elevated intracranial pressure

Abstract: The non-invasive ICP measurement method based on two-depth TCD technology has a better diagnostic reliability on neurological patients than the ONSD method when expressed by the sensitivity and specificity for detecting elevated ICP >14·7 mmHg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 35 publications
2
42
0
3
Order By: Relevance
“…Non-invasive ICP was measured in a supine position using the two-depth transcranial Doppler (TCD) device, which sensitivity, specificity and diagnostic value were proven in the previous studies with neurological patients 15. A head frame with a fixed ultrasound transducer for placement over the closed eyelid was positioned on a patient’s head.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-invasive ICP was measured in a supine position using the two-depth transcranial Doppler (TCD) device, which sensitivity, specificity and diagnostic value were proven in the previous studies with neurological patients 15. A head frame with a fixed ultrasound transducer for placement over the closed eyelid was positioned on a patient’s head.…”
Section: Methodsmentioning
confidence: 99%
“…The non-invasive ICP technology uses Doppler ultrasound for simultaneous insonation angle-independent blood flow pulsation monitoring in the intracranial and extracranial segments of the ophthalmic artery (OA). This method allows for direct comparison of ICP value with the value of external pressure (Pe) that is applied to the tissues surrounding the eyeball 15. By implementing this technique, we aim to assess for differences in the neuroretinal rim area (NRA) and ocular haemodynamic parameters in patients with NTG with differing ICP values.…”
Section: Introductionmentioning
confidence: 99%
“…However, the withinpatient variation was similar to the total variation (Table 2); therefore, precision greater than ± 8 mmHg can not be expected in elderly patients. A recent report using our noninvasive method showed promising results in a younger population, but only a few patients had ICPs above 20 mmHg [33].…”
Section: Discussionmentioning
confidence: 92%
“…Ragauskas et al found that TCD was a superior indicator of ICP > 14.7 mmHg compared to ultrasound-measured ONSD; ONSD with a cutoff value of 5.0 mm yielded a sensitivity of 37.0 %, specificity of 58.5 %, and AUC = 0.57, while TCD demonstrated a sensitivity of 68.0 %, specificity of 84.3 %, and AUC = 0.87 [73]. A number of studies have found that PI and ICP are highly correlated with correlation coefficients ranging from 0.89 to 0.938 [74,75]; similarly, Hunter et al found that the change in ICP was correlated with the change in PI before and after CSF withdrawal in patients with suspected idiopathic intracranial hypertension (p = 0.004) [76].…”
Section: Functional Modalities Transcranial Doppler Ultrasonography (mentioning
confidence: 95%
“…Skau et al[68] ▪ Comparison to ICP measured via lumbar puncture (LP)Kalantari et al[32] ▪ No comparison to invasively measured ICP ▪ ONSD measured by CT and ONSD measured by MRI correlate strongly with r = 0.8941Ocular ultrasound vs. CTOhle et al[108] ▪ No comparison to invasively measured ICP ▪ Meta-analysis with 12 studies ▪ ONSD determined by ocular ultrasound is 95.6 % sensitive and 92.3 % specific for CT findings suggestive of increased ICP (ex. shift, collapse of ventricles, intracranial bleeding of greater than 2 mm) ▪ ONSD cutoff values:Ragauskas et al[73] ▪ Comparison to ICP measured via lumbar puncture (LP) ▪ Elevated ICP defined as ICP > 14.7 mmHg…”
mentioning
confidence: 99%